Quick and low-cost high resolution remote sensing using UAV and aircraft to address initial stage of disaster response. Issue 1 (June 2020) - Sugita, S; Fukui, H; Inoue, H; Asahi, Y; Furuse, Y
Abstract: The experiments of aerial photogrammetry using UAV and aircraft are demonstrated to compare their performance and resolution. Instruments used for the aircraft photogrammetry is commercial product digital camera. This is much lower-cost than professional photogrammetry instruments, however the results shows enough quality for information gathering in the initial stage of disaster response. On the other hand, The UAV aerial photo sharing web system "UAV oblique photo browser" has been newly developed as a light weight and simple system that is useful in the initial stage of disaster response.